(untitled) (Heritage, 2023)
During the archaeological research of the forum in Municipium DD, remains of Antique architecture were discovered, including fragments of architectural sculpted decorations The most important part of the research documentation are archaeological journals and Emil Čerškov’s monograph, which provided an insight into the number, type and position of these architectonic decoration. This paper provides a first overview and architectural analysis of the known fragments of sculptural decorations, with the goal of determining which constructions in the forum they belonged to. They comprise two groups of fragments, differing by their stylistic traits, typological and chronological determination. The first group comprehends those that were both parts of architectural decorations and constructive elements of the Temple of Antinous, belonging to the 2nd century architecture. The second group contains re-hewn parts of gravestones, used as opening elements of constructions built from the end of the 3rd – beginning of the 4th century. The shaping of the decoration from the Temple of Antinous completely corresponds to the cannons of the ionic order. A capital belonging to type D of Asia Minor ionic capitals (classification by Оrhan Bingӧl) stands out. One of the most interesting decoration examples is a cornice with a bucranion and garlands, completely obliterated today. Although we determine that with certainty, the archaeological context and common use of this motif on temples and altars suggest that it belonged to the Temple of Antinous. Hewn parts of the temple belong to the conservative design of classical architecture, completely unknown in these regions before the Roman conquest. Traits of autochthonous (Dardanian) architecture cannot be noted. As a minor provincial town, Municipium DD obviously accepted all models from Asia Minor with established stonemasonry traditions in the 2nd century.